Risk Management of Grocery Businesses in the Tegal Region Using an ISO 31000-Based Approach: Management of Grocery Businesses in the Tegal Region Using an ISO 31000-Based Approach - Amirah; Retno Wulandari (Universitas Indo Global Mandiri Palembang, 2025)
AbstractObjective: This study aims to analyze various risks faced by grocery businesses in the Tegal area using anISO 31000-based risk management approach.Design/Methods/Approach: The research method used was descriptive quantitative, involving 50 MSMEgrocery business actors in the Tegal area who were selected using purposive sampling techniques. Data wascollected through questionnaires using a Likert scale and analyzed through the stages of identification,analysis, evaluation, and risk management in accordance with the ISO 31000 standard.Findings: The results of the study show that six major risks are in the high category, namely the emergenceof competitors, customer decline, theft, changes in government regulations, and price fluctuations. Fourother risks are in the moderate category, namely recording errors, damaged or expired goods, stockshortages, and disaster risks. Risk management is largely at a high level of efficiency, although some risksare still at a moderate level and still require mitigation reinforcement.Originality/Value: This study provides added value through the application of ISO 31000 to small andmedium-sized grocery businesses, a context that has not been widely studied. This study presents a morestructured risk mapping, thereby enriching the literature on risk management in small-scale retailbusinesses.Practical/Policy implication: The application of ISO 31000 helps grocery businesses determine riskpriorities, improve risk management effectiveness, and increase business operational resilience tobusiness environment uncertainties. Keywords: ISO 31000, Risk Management, MSMEs, Grocery Businesses